2010
DOI: 10.1073/pnas.1005439107
|View full text |Cite
|
Sign up to set email alerts
|

BK channels play a counter-adaptive role in drug tolerance and dependence

Abstract: Disturbance of neural activity by sedative drugs has been proposed to trigger a homeostatic response that resists unfavorable changes in net cellular excitability, leading to tolerance and dependence. The Drosophila slo gene encodes a BK-type Ca 2+ -activated K + channel implicated in functional tolerance to alcohol and volatile anesthetics. We hypothesized that increased expression of BK channels induced by these drugs constitutes the homeostatic adaptation conferring resistance to sedative drugs. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…Ethanol increased slowpoke expression in the nervous system coincident with the induction of ethanol tolerance (Cowmeadow et al, 2006). Since an increase of slowpoke expression is also caused by cold, by CO 2 sedation (Ghezzi et al, 2010) or by heat-shock promoters (Cowmeadow et al, 2006) it was suggested that this is a more common mechanism for acquisition of tolerance. Interestingly the Drosophila slowpoke gene appears to contain a binding site for CREB (cyclic-AMP response element binding protein) which has been implicated in learning and memory and hence may also be involved in the ethanol response (Cowmeadow et al, 2006) and possibly in the memory deficits after excessive alcohol intake.…”
Section: Bk Channels -And Ethanol Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol increased slowpoke expression in the nervous system coincident with the induction of ethanol tolerance (Cowmeadow et al, 2006). Since an increase of slowpoke expression is also caused by cold, by CO 2 sedation (Ghezzi et al, 2010) or by heat-shock promoters (Cowmeadow et al, 2006) it was suggested that this is a more common mechanism for acquisition of tolerance. Interestingly the Drosophila slowpoke gene appears to contain a binding site for CREB (cyclic-AMP response element binding protein) which has been implicated in learning and memory and hence may also be involved in the ethanol response (Cowmeadow et al, 2006) and possibly in the memory deficits after excessive alcohol intake.…”
Section: Bk Channels -And Ethanol Tolerancementioning
confidence: 99%
“…The drugs increased expression of the slo gene, enhanced neuronal excitation by reducing the refractory period between action potentials and augmented seizure susceptibility (Ghezzi et al, 2010). Mutant BK channels exhibiting increased activity were found in humans to cause increased excitability due to rapid repolarization of action potentials (Du et al, 2005).…”
Section: Bk Channels -And Ethanol Tolerancementioning
confidence: 99%
“…The drug induced enhancement of the Ca 2+ -activated K + channel activity causes resistance to sedation by increasing neural excitability. In Drosophila, sedative exposure to alcohols and volatile anesthetics have been shown to inhibit neural excitability, at least in part, by increasing the neuronal refractory period and thus reducing the capacity for repetitive firing (Lin and Nash 1996; Ghezzi et al 2010). Meanwhile, increased slo expression was shown to decrease the neuronal refractory period and enhance repetitive firing, thereby opposing the acute effects of acute drug sedation (Ghezzi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, sedative exposure to alcohols and volatile anesthetics have been shown to inhibit neural excitability, at least in part, by increasing the neuronal refractory period and thus reducing the capacity for repetitive firing (Lin and Nash 1996; Ghezzi et al 2010). Meanwhile, increased slo expression was shown to decrease the neuronal refractory period and enhance repetitive firing, thereby opposing the acute effects of acute drug sedation (Ghezzi et al 2010). After drug clearance however, the slo -dependent increase in neural excitability persists and results in an increase in seizure susceptibility—a symptom typical of severe alcohol withdrawal (Ghezzi et al 2010; Ghezzi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In rodent models, acute ethanol exposure leads to reduced vasopressin, oxytocin and growth hormone release with consequent perturbation in physiology and behavior (7), altered firing rates in nucleus accumbens (8) and dorsal root ganglia neurons (9), and alcohol-induced cerebral artery constriction (10,11). Moreover, studies in both mammals and invertebrate models demonstrate that ethanol targeting of neuronal BK is involved in development of alcohol tolerance and dependence (12)(13)(14)(15)(16). Although the physiological and behavioral consequences of ethanol disruption of BK function have been well documented, it remains unknown whether alcohol modification of BK function results from drug interaction with a defined recognition site(s) in a protein target vs. physical perturbation of the proteolipid environment where the BK protein resides.…”
mentioning
confidence: 99%